PENGARUH LAMANYA PENGOMPOSAN PADA MEDIA TANAM DENGAN PENAMBAHAN EM-4 TERHADAP PERTUMBUHAN JAMUR TIRAM (Pleurotus ostreatus) DAN POTENSINYA SEBAGAI SUMBER BELAJAR PADA MATERI BIOTEKNOLOGI KELAS XII SMA - Sista, Dini Hariani; Zulfarina, Zulfarina; Suryawati, Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of composting on planting media with the addition of EM-4 to the growth of oyster mushrooms (Pleurotus ostreatus) and produce learning resources in the form of learning videos in class XII high school biotechnology material. This research was conducted at the Biology Mushroom House Laboratory of Biology Education FKIP UNRI in May-December 2019. This research was carried out in 2 stages: the experimental stage: the influence of the duration of composting on planting media with the addition of EM-4 to the growth of oyster mushrooms (Pleurotus ostreatus) and the stages learning resources design: analysis of the potential and development of instructional video designs from the results of research. The study used an experimental method with 2 factorial Completely Randomized Design (CRD) consisting of 12 treatments and 3 replications. The parameters in this study are the mycelium growth rate, analysis of the number of fruit bodies, wet weight, dry weight and moisture content. The duration of composting for 5 days with the addition of EM-4 as much as 10 ml/baglog (P2E2) is the best treatment and based on the analysis of the potential results of the study can be used as a video design of biotechnology learning materials for class XII high school.Key Words: Length of Composting, EM-4, Growth of Oyster Mushrooms, Learning Video